Environmental, Social, and Governance, Investment, and Firm Value: Insights from a Bibliometric and Systematic Review - Auliyah Rizky Suhasmoro; Tanti Novianti; Noer Azam Achsani; Trias Andati (Penerbit Goodwood, 2026)
Purpose: This study synthesizes the literature on the relationship between Environmental, Social, and Governance (ESG) factors, investment outcomes, and firm value. Despite the growth of ESG research, the findings remain fragmented, particularly regarding which ESG dimensions are materially relevant for valuation and investment decisions. Research Methodology: A systematic literature review combined with a bibliometric analysis was conducted using the Scopus database. A total of 67 peer-reviewed journal articles published between 2017 and 2025 were selected based on predefined inclusion criteria, including relevance, accessibility, and journal quality (Q1–Q2 journals). Bibliometric techniques—keyword co-occurrence, author co-citation, and bibliographic coupling—were performed using VOSviewer to identify the key themes and intellectual foundations. Results: The results show a sharp rise in ESG-related research after 2021, with a 35% increase in the number of publications. Themes such as ESG performance, corporate governance, and firm valuation metrics, such as Tobin’s Q, are central. However, studies relying on aggregate ESG scores dominate, and research on specific ESG indicators and dynamic ESG risks, such as controversies, is limited. Conclusions: The findings reveal substantial heterogeneity across institutional and market contexts, explaining the inconsistent empirical evidence. ESG research has grown significantly, but more granular and context-sensitive studies are needed to explore the varying impacts across industries and regions. Limitations: This study was limited to Scopus-indexed, English-language, open-access Q1–Q2 journal articles and did not assess causal relationships. This may exclude relevant studies from non-English journals or other sources. Contributions: This study provides a bibliometric synthesis of ESG investment firm value research, highlighting gaps and encouraging future studies focused on indicator-specific ESG measures and dynamic risks.